Computational simulation of cross-flow of Williamson fluid over a porous shrinking/stretching surface comprising hybrid nanofluid and thermal radiation - Umair Khan; Aurang Zaib; Sakhinah Abu Bakar; Anuar Ishak; Dumitru Baleanu; El-Sayed M Sherif (AIMS Mathematics, 2022)
Recent nanotechnology advancements have created a remarkable platform for the development of a better performance of ultrahigh coolant acknowledged as nanofluid for numerous industrial and engineering technologies. The current study aims to examine the boundary-layer cross-flow of Williamson fluid through a rotational stagnation point towards either a shrinking or stretching permeable wall incorporated by a hybrid nanofluid. The shape factors along with the radiation effect are also taken into account. The contained boundary layers are the type of stream-wise by shrinking/stretching process along with the sheet. Employing the suitable transformations, the partial differential equations (PDEs) are transmuted to similarity (ordinary) differential equations (ODEs). The transmuted system of ODEs is worked out by using a built-in package bvp4c in MATLAB for distinct values of pertaining parameters. Dual (first and second branch) outcomes are found for the shrinking surface. The results suggest that the inclusion of hybrid particles uplifts the drag force as well as the heat transfer in both solutions. In addition, the Weissenberg number accelerates the separation. Moreover, the effect of suction permits the friction factor and heat transfer to improve significantly at the porous shrinking/stretching sheet of hybrid nanofluid.